Rare bleeding disorders – bleeding assessment tools, laboratory aspects and phenotype and therapy of FXI deficiency. (May 2014) - James, P.; Salomon, O.; Mikovic, D.; Peyvandi, F.
Summary: Rare bleeding disorders (RBDs) are inherited deficiencies of coagulation factors such as fibrinogen, factor (F) II, FV, FVII, combined FV+FVIII, FX, FXI and FXIII. These disorders usually have a low prevalence in the general population and constitute approximately 3–5% of all coagulation disorders. However, in some countries they may have the same prevalence as haemophilia B due to the practice of consanguineous marriage. The clinical picture of RBDs is highly variable and can vary markedly from mild to severe, making both diagnosis and optimal treatment quite challenging. This review focuses on: (i) the efforts to establish a bleeding assessment tool adequate to RBDs, (ii) the optimal management of patients affected with FXI deficiency and (iii) the correlation between clinical severity and laboratory diagnosis when determining the minimum coagulant activity required to prevent bleeding in each RBD.